2011
DOI: 10.1029/2010wr009104
|View full text |Cite
|
Sign up to set email alerts
|

Examination of change factor methodologies for climate change impact assessment

Abstract: [1] A variety of methods are available to estimate values of meteorological variables at future times and at spatial scales that are appropriate for local climate change impact assessment. One commonly used method is Change Factor Methodology (CFM), sometimes referred to as delta change factor methodology. Although more sophisticated methods exist, CFM is still widely applicable and used in impact analysis studies. While there are a number of different ways by which change factors (CFs) can be calculated and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(198 citation statements)
references
References 35 publications
2
196
0
Order By: Relevance
“…There are a number of other bias correction methods that can be used to account for the systematic mismatch between observed and simulated climate variables (e.g. Anandhi et al 2011, Stoll et al 2011, Sulis et al 2012. Assessments of different techniques and their limitations can be found in Hagemann et al (2011) and Ehret et al (2012).…”
Section: 23mentioning
confidence: 99%
“…There are a number of other bias correction methods that can be used to account for the systematic mismatch between observed and simulated climate variables (e.g. Anandhi et al 2011, Stoll et al 2011, Sulis et al 2012. Assessments of different techniques and their limitations can be found in Hagemann et al (2011) and Ehret et al (2012).…”
Section: 23mentioning
confidence: 99%
“…The so-called "delta change" or perturbation method belongs to this type of approach (Anandhi et al, 2011;Ruelland et al, 2012): it consists in perturbing the observed precipitation and temperature series to reproduce the changes observed between the control and future climatic simulations from climate models. The hypothesis behind is that climate models are not necessarily good at reproducing the present climate in a realistic manner (contrary to weather forecast models, they do not assimilate observations for example) but are mainly designed to simulate the trends of the earth climate system related to external forcing (green-house gases, aerosols, solar variation, volcanic eruption).…”
Section: Y Tramblay Et Al: a First Evaluation Of The Aladin-climatementioning
confidence: 99%
“…CFM is a very common method for estimating climate change (Anandhi et al, 2011). Although more complicated methods exist, CFM is still widely applied in many studies.…”
Section: Change Factor Methods (Cfm)mentioning
confidence: 99%
“…Different mathematical formulations are used for different variables. For example, additive change factor (CF) is often used for temperature and multiplicative CF is often used for precipitation (Anandhi et al, 2011). Multiplicative is also used for standard deviation of temperature.…”
Section: Change Factor Methods (Cfm)mentioning
confidence: 99%